2021
DOI: 10.26911/thejhpb.2021.06.01.06
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Clean and Healthy Behavior, Social Capital, and Nutritional Status in Children Under Five in Waingapu Health Center

Abstract: Background: Quality nutrition is a determinant of children's survival, health, and growth. Nutritional problems and lack of nutrient intake are also about whether bad in the environment or commonly known as clean and healthy behavior. Social capital refers to social relationships and connections between individuals because it is more of a relationship between individuals than an individual attribute. This study aimed to examine the relationship between clean and healthy behavior and social capital with the nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A study conducted in one of the Public Health Center's working areas in Indonesia discovered a link between a clean and healthy lifestyle and nutritional status with a p-value=0.0001 [40]. According to this study, research conducted in East Sumba found that a clean and healthy lifestyle has a strong correlation with nutritional status and can improve good nutritional status with pvalue <0.05 [41]. As seen from the finding, it is evident that fishermen's families in the Mandeh area tend to do light physical activity.…”
Section: Factors Affecting Nutritional Balancementioning
confidence: 79%
“…A study conducted in one of the Public Health Center's working areas in Indonesia discovered a link between a clean and healthy lifestyle and nutritional status with a p-value=0.0001 [40]. According to this study, research conducted in East Sumba found that a clean and healthy lifestyle has a strong correlation with nutritional status and can improve good nutritional status with pvalue <0.05 [41]. As seen from the finding, it is evident that fishermen's families in the Mandeh area tend to do light physical activity.…”
Section: Factors Affecting Nutritional Balancementioning
confidence: 79%